Post-cyclone livelihood status and strategies in coastal Bangladesh - Paul, Shitangshu Kumar (Rajshahi University Journal of Life & Earth and Agricultural Sciences, 2015)
The objective of this paper is to assess post-cyclone livelihood capitals status, identify major livelihood groups, adversity and crisis, and present the livelihood strategies of coastal households. Based on a questionnaire survey at household level, a total 331 out of 792 households are selected through simple random sampling from three purposively selected villages in the central coast of Bangladesh. Both descriptive and inferential statistics are used to analyse data. The present study identifies wage labour, fisher and farmer as major livelihood groups. Among the three villages, Island reveals less livelihood capitals than inland and shoreline. Although natural capital of Island is relatively higher, however, scarcity of other capitals hinders proper utilization of the potentials of such capital. Social capital of Island is significantly lower than other two villages, which unveils relatively lesser social coherence of Islanders, and which is most important to survive in post-cyclone situation. Likewise, among the livelihood groups, wage labourer owes less livelihood capitals than farmer and fishermen. Majority of the households irrespective of their village locations identifies recurrent cyclones and induced storm surges as major adversities which significantly destroys their livelihoods. Therefore, households in study villages diversify income sources wherever possible and most importantly while face the crisis. In general, livelihoods of Islanders and Shoreline villagers, wage labourer and fish fry collectors are most vulnerable to any cyclone events. Hence, the present study advocates for identifying vulnerable locations and livelihood groups, and livelihood capitals building for such groups and promoting coordinated disaster risk reduction programs to mitigate cyclone impacts and providing assistance for rebuilding post-cyclone livelihoods.